Polarization study in Newtonian telescope components for depolarization parameter correction in atmospheric LiDAR (2023)
In the present work, an experimental system is implemented, and a theoretical model is built that allows quanti fying atmospheric depolarization in the city of Santiago de Cali, Colombia. The experimental setup uses a LiDAR coupled to a Polarotor, which allows the separation of the backscattered light into its parallel and perpendicular polarization components. This device allows the use of a single photomultiplier tube, thus facilitating calibration procedures. The theoretical model is based on the Mueller formalism and considers the contribution of each op tical element of the LiDAR system on the polarization of the backscattered light. This is achieved by assigning to each element a Mueller matrix and subsequently calculating the matrix associated with the whole assembly. The contribution of the optical elements of the system on the depolarization parameter d is determined. The corrections to the signals obtained are established, so that the data is not altered by the particularities of the assembly used.